Gene Therapy, Early Promises, Subsequent Problems, and Recent Breakthroughs - Saeideh Razi Soofiyani; Behzad Baradaran; Farzaneh Lotfipour; Tohid Kazemi; Leila Mohammadnejad (Tabriz University of Medical Sciences, 2013)
Gene therapy is one of the most attractive fields in medicine. The concept of gene delivery to tissues for clinical applications has been discussed around half a century, but scientist's ability to manipulate genetic material via recombinant DNA technology made this purpose to reality. Various approaches, such as viral and non-viral vectors and physical methods, have been developed to make gene delivery safer and more efficient. While gene therapy initially conceived as a way to treat life-threatening disorders (inborn errors, cancers) refractory to conventional treatment, to date gene therapy is considered for many non-life-threatening conditions including those adversely influence on a patient's quality of life. Gene therapy has made significant progress, including tangible success, although much slower than was initially predicted. Although, gene therapies still at a fairly primitive stage, it is firmly science based. There is justifiable hope that with enhanced pathobiological understanding and biotechnological improvements, gene therapy will be a standard part of clinical practice within 20 years.